Chimenea solar con acumulación de calor para acondicionamiento térmico pasivo de edificios - Kosut Cia, Juan Pablo (2017)
A solar chimney is a device able to convert solar energy into mechanical energy, in which an air circulation is generated by natural convection. The analysis of its operating mechanism is of great interest due to the economical and environmental advantages that it can provide for thermal conditioning and ventilation in buildings. In this work, analytical models presented in the literature for the estimation of the airflow produced by a solar chimney were reviewed. The theoretical concepts involved in the models were identified, and the agreement with the experimental measurements was analyzed. It was shown that, despite most analytical models calculate the airflow by balancing buoyancy forces with pressure loses, this methodology is not adequate in certain flow regimens. A new methodology, based on the plume method, introduced by He et al., 2016 was proposed for the pressure loses calculation, taking into account different flow regimens present in the solar chimney, depending on the geometry and the incident solar radiation. A simplified numerical model was implemented in FORTRAN. It was able to solve heat transfer in solid components of the chimney, and heat, momentum and mass conservation equations for the air. The numerical model was validated, showing a better fit to the experimental measurements than the existing analytical models.